2022
DOI: 10.2166/wst.2022.284
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antimicrobials in anammox mediated systems: critical review

Abstract: Anammox-mediated systems are thought to be cost-effective and efficient technologies for removing nitrogen from wastewater by converting nitrite and ammonium into dinitrogen gas. However, there are inhibitory substances that reduce the effectiveness and efficiency of these processes, preventing their widespread application. Antimicrobial agents are among these substances that have been observed to inhibit anammox-mediated processes. Therefore, this review provides a comprehensive overview of the effects of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…The results demonstrated that multiantibiotic exposure inhibited TN removal performance in the anammox process, especially under high nitrogen load conditions, and the inhibition tended to be irreversible. Anammox inhibition by OTC is reportedly caused by cell membrane damage and protein synthesis inhibition, while SDZ inhibits bacterial growth and reproduction by competing with p -aminobenzoic acid in the enzymatic synthesis of dihydrofolic acid. , Nevertheless, the impacts of OTC or SDZ on anammox depend on the antibiotic concentration. Anammox was reportedly inhibited when the OTC concentration reached 2 mg/L .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results demonstrated that multiantibiotic exposure inhibited TN removal performance in the anammox process, especially under high nitrogen load conditions, and the inhibition tended to be irreversible. Anammox inhibition by OTC is reportedly caused by cell membrane damage and protein synthesis inhibition, while SDZ inhibits bacterial growth and reproduction by competing with p -aminobenzoic acid in the enzymatic synthesis of dihydrofolic acid. , Nevertheless, the impacts of OTC or SDZ on anammox depend on the antibiotic concentration. Anammox was reportedly inhibited when the OTC concentration reached 2 mg/L .…”
Section: Resultsmentioning
confidence: 99%
“…Anammox inhibition by OTC is reportedly caused by cell membrane damage and protein synthesis inhibition, while SDZ inhibits bacterial growth and reproduction by competing with p-aminobenzoic acid in the enzymatic synthesis of dihydrofolic acid. 8,29 Nevertheless, the impacts of OTC or SDZ on anammox depend on the antibiotic concentration. Anammox was reportedly inhibited when the OTC concentration reached 2 mg/L.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher temperatures promote the growth of thermophilic bacteria, which degrade certain compounds more efficiently. However, extreme temperatures, both hot and cold, have negative impacts on microbial activity and reduce treatment performance [ 98 , 99 ].…”
Section: Operating Parameters Of Ifasmentioning
confidence: 99%